Economic growth, 'globalisation' and labour power. (23rd May 2007) - Altman, Morris
A contentious populist belief maintains that increasing international trade or economic 'globalisation', has deleterious effects upon the economic welfare of the vast majority of the world's population. Such negative effects are an inevitable consequence of capitalism, especially that which embraces globalisation. I argue that this anti-globalisation-trade-market hypothesis is fundamentally flawed. Increasing trade and other attributes of globalisation has the capacity to enhance the bargaining power of labour and thereby economic efficiency and the rate technological change with significant resulting benefits flowing to labour. Tight labour markets can be regarded as a key capability allowing for workers to improve their welfare. But institutions must be in place to allow labour to capitalise on its market generated advantage. Unlike many neoclassical renderings of the globalisation narrative, positive effects of globalisation are in no ways guaranteed and optimised by market forces.